Problems of legal regulation and improving its effectiveness - Baizhanova, K.T. Baizhanova; Serikbayeva, S.S. (Bulletin of the Karaganda University “Law Series”, 2024)
The article is devoted to the analysis of scientific approaches characterizing the essence of socio-legal phenomena concerning the issues of legal regulation and increasing its effectiveness. The purpose of the study is to identify the main elements of legal regulation, interrelationships between them, as well as methods of legal regulation on the basis of analysis and systematization of various approaches to legal regulation, theoretical provisions, principles recognized in legal science; development of an algorithm to identify errors in legal regulation. The object is legal regulation, considered as a system; the subject is the general structural and functional regularities of legal regulation. The peculiarities of this study, which constitute a number of differences from other works written on the topic of legal regulation: first, legal regulation is considered as a system consisting of static and dynamic elements. Secondly, a systematic approach to the analysis of the category of legal regulation is applied. Thirdly, the elements of legal regulation are analyzed at the general theoretical level. A number of basic interrelations and functions of legal regulation and legal impact are singled out, and on the basis of the above, generalized results of legal regulation are formulated, allowing to identify errors in legal regulation and indicate ways to eliminate them.